Pengaruh Lingkungan Sekolah, Teman Sebaya dan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada SMK Bidang Manajemen Bisnis Jurusan Pemasarandi Kecamatan Jambi Selatan Kota Jambi - Redi Indra Yudha; Idris idris (Program Magister Pendidikan Ekonomi (S2), 2014)
The purpose of this study is to determine the effect of the school environment, peers, and study motivation on the student achievement in SMK business management marketing majors south jambi subdistrict jambi city. By using proportional random sampling technique analysis, the obtained of samples with the number of students is 109. The results showed, in the school environment to support Based on the research results, it can be concluded that in a school environment in order to support the smooth implementation of the learning process, should be able to pay attention to the need for means of support. Thus, students can develop their skills with the help of friends his age to be more motivated to improve learning outcomes, especially in the field of vocational students of business management marketing majors south jambi subdistrict jambi city. Keyword : School Environment, Peers, Study Motivation, Study Achievement.